IMPLEMENTASI PEMBIASAAN LAGU INDONESIA RAYA SEBAGAI MEDIA INTEGRASI NILAI-NILAI KEISLAMAN DAN NASIONALISME DI MAN 1 KOTA PROBOLINGGO - Fatimatus Zahro; Agatha Lola Margareta; Nur Izzatis Sa’idah; Mardiana; Danisatun Sakdia; Nazahah Ulil Nuha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of the habitual singing of the Indonesian national anthem, Indonesia Raya, as a medium for integrating Islamic values and nationalism at MAN 1 Kota Probolinggo. This research is motivated by the declining sense of nationalism among students, influenced by the pressures of globalization and modernity. Using a qualitative approach through observation, interviews, and documentation, data were collected from the school principal, Islamic Education (PAI) teacher, Civics (PPKn) teacher, OSIS advisor, and students directly involved in the activity. The findings show that the consistent practice of singing Indonesia Raya effectively strengthens students’ national awareness, discipline, and respect for national symbols. Although some students initially appeared reluctant or less enthusiastic, continuous habituation supported by teacher role models and school policies gradually shaped positive behavioral changes. Informants emphasized that students require strong figures and a supportive environment to internalize both national and religious values. These results align with habit formation theory, Bandura’s social-cognitive theory on modeling, and Lickona’s character education framework. The study concludes that the habituation of singing Indonesia Raya is effective in reinforcing nationalism and integrating Islamic values within the school environment. The research is limited in scope, indicating the need for broader future studies and potential incorporation of quantitative methods for deeper analysis.